Our Impact 2016-2017 Program Focus Team Report - Hadley, Gregg (My University, 2018)
K-State Research and Extension's program report for 2016-2017. This report to a variety of stakeholders illustrates the statewide extension work for the programming year.
Keywords: Administrative and Research Reports